Iron-cobalt-based amorphous nanocrystalline soft magnetic alloy and preparation method thereof

By using iron-cobalt-based amorphous nanocrystalline soft magnetic alloy and preparing amorphous strips through a single-roll quenching method, the shortcomings of existing iron-based amorphous/nano-crystalline alloys in saturation magnetic induction strength and thermal stability are solved, and the problem of the existing iron-based amorphous/nano-crystalline alloys is achieved. It is a high-performance magnetic material within a wide heat treatment temperature range, suitable for industrial applications.

CN119464969APending Publication Date: 2025-02-18HEFEI UNIV OF TECH

Patent Information

Application Number
CN202510061521.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing iron-based amorphous/nano-crystalline alloys have shortcomings in saturated magnetic induction strength and thermal stability, resulting in their limitations in industrial applications.

Method used

An iron-cobalt-based amorphous nanocrystalline soft magnetic alloy is used, and its atomic percentage is FexCoySiaBbPcCdCue. The amorphous strip is prepared by a single-roll quenching method, and annealed in a wide heat treatment temperature range to form a nanocrystalline structure.

Benefits of technology

It realizes the maintenance of high saturation magnetic induction strength and low coercivity within a wide heat treatment process window, reduces raw material costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464969A_ABST
    Figure CN119464969A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-cobalt-based amorphous nanocrystalline soft magnetic alloy and a preparation method thereof, and relates to the technical field of nanocrystalline alloys.The iron-cobalt-based amorphous nanocrystalline soft magnetic alloy comprises an amorphous matrix and nanocrystalline distributed on the amorphous matrix in a dispersed mode, the chemical expression of the iron-cobalt-based amorphous nanocrystalline soft magnetic alloy is FexCoySiaBbPcCdCue, x, y, a, b, c, d and e in the formula respectively represent the atom percentage content of all corresponding components, wherein 6 < = c < = 10, 0 < = e < = 1, and x + y + a + b + c + d + e = 100. The preparation method comprises the following steps: mixing the raw materials according to the atomic percentage, smelting, preparing a molten master alloy ingot into an amorphous alloy strip by adopting a single-roller quenching method, cutting, wrapping with tinfoil, and carrying out annealing heat treatment in an annealing furnace. According to the iron-cobalt-based amorphous nanocrystalline magnetically soft alloy, a wide heat treatment process window can be obtained through component regulation and control, the iron-cobalt-based amorphous nanocrystalline magnetically soft alloy can be suitable for industrial production, and the iron-cobalt-based amorphous nanocrystalline magnetically soft alloy has good soft magnetic performance and can become a new material in the high-frequency working field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocrystalline alloys, and in particular to an iron-cobalt-based amorphous nanocrystalline soft magnetic alloy and a preparation method thereof. Background Art

[0002] Iron-based amorphous / nanocrystalline alloys are favored for their excellent soft magnetic properties, such as high saturation flux density ( B s ), low coercivity ( H c ), low core loss, etc., which can significantly reduce the energy loss in the electromagnetic conversion process and has attracted widespread attention. Therefore, it is used in transformer cores, motors and electronic components, which shows that iron-based amorphous / nanocrystalline alloys are potential candidates for energy-saving and low-carbon materials in future industrial applications. However, the current problem with this material is that its low saturation magnetization intensity ( B s ) is 70 ~ 80% of silicon steel (i.e. ≈1.4 ~ 1.6 T). The material obtained in the initial state is amorphous. Annealing at low temperature (annealing depends on the main components) can lead to the precipitation of nanocrystalline grains in the amorphous matrix, so it is called amorphous / nanocrystalline alloy. But at the same time, it has a high saturation flux density ( B s )'s iron-based amorphous and nanocrystalline alloys have not yet been industrialized on a large scale due to their low amorphous forming ability (GFA).

[0003] In order to improve the saturation magnetic induction intensity of Fe-based amorphous nanocrystals ( B s ), scholars have explored two methods to increase the saturation magnetic induction intensity in related nanocrystalline alloys such as Finemet (Fe-Si-B-Cu-Nb), Nanoperm (Fe-MB) and Hitperm (Fe(Co)-MB-Cu), where M=Zr, Nb, Hf alloys. One is to increase the mass percentage of Fe element in the system, and the other is to introduce Co element into the nanocrystalline system so that the system forms Fe-Co atomic pairs. In the former method, when the atomic percentage of Fe element in the system exceeds 85%, the soft magnetic properties of the entire system will deteriorate. Not only will its saturation magnetic induction intensity decrease, but the amorphous forming ability will also weaken. At this time, the α-Fe phase and the amorphous matrix will coexist, and the coercive force will increase sharply. The reason is that the reduction in amorphous forming ability leads to an increase in structural order, which increases the density of quasi-dislocation dipole stress sources or the pinning ability generated by elastic stress, thereby increasing the coercive force. The second method, increasing the proportion of ferromagnetic elements in the alloy can improve the nanocrystalline alloy. B sSince Co has a higher exchange integral strength, adding an appropriate amount of Co to Fe-based nanocrystalline alloys can enhance the ferromagnetic exchange coupling effect and improve the alloy B s .

[0004] In 2014, Rui Xiang et al. introduced 29%~54% Co atoms into the Fe-Si-BP-Cu system. The results showed that the addition of Co reduced the thermal stability of the amorphous phase, thereby increasing the heat treatment temperature of the alloy. After proper annealing at 763 K for 10 min, an α-FeCo phase-dispersed Fe-Co-Si-BP-Cu nanocrystalline alloy was obtained. The α-FeCo grain size in the primary crystal was between 9 and 28 nm. In 2020, Tianhao Jiang et al. studied the effects of Cu addition and annealing temperature on Fe 81 B 13 The results show that Fe 81 B 13 P3Si2C1 and (Fe 81 B 13 P3Si2C1) 99 Cu1 amorphous / nanocrystalline alloys have excellent soft magnetic properties. The addition of a small amount of Cu can expand the temperature interval between the first and second crystal temperatures from 48 K to 112 K, expand the processing window of amorphous alloys, and improve the thermal stability of amorphous alloys.

[0005] In summary, the soft magnetic amorphous nanocrystalline alloys with high saturation magnetic induction intensity currently developed have poor amorphous forming ability, a relatively small heat treatment temperature range for optimal soft magnetic properties, and poor thermal stability, which greatly hinders the industrial application of amorphous strips.

[0006] Therefore, the present invention provides an iron-cobalt-based amorphous nanocrystalline soft magnetic alloy having excellent soft magnetic properties, strong amorphous forming ability and suitable for industrial production. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides an iron-cobalt based amorphous nanocrystalline soft magnetic alloy and a preparation method thereof. The alloy can have good saturation magnetic induction intensity and low coercive force in a wide heat treatment process window, does not contain the addition of expensive metals such as Nb and Mo, thereby reducing the cost of raw materials. At the same time, the amorphous ribbon prepared by single-roll spinning has strong amorphous forming ability, the preparation process is simple, and is suitable for industrial production and application.

[0008] To achieve this object, the present invention adopts the following technical solutions: One of the purposes of the present invention is to provide an iron-cobalt-based amorphous nanocrystalline soft magnetic alloy, wherein the iron-cobalt-based amorphous nanocrystalline soft magnetic alloy has the following atomic percentage expression: Fe x Co y Si a B b P c C d Cu e ; Wherein, x, y, a, b, c, d and e represent the atomic percentage of the corresponding element respectively, 60≤x≤70, 15≤y≤25, 3<a≤6, 4<b≤7, 6≤c≤10, 0<d≤1.5, 0≤e≤1, x:y=(3~5):1, and x+y+a+b+c+d+e=100.

[0009] Here, 0≤e≤1 indicates that the embodiment includes a comparison of the properties of two alloys containing Cu and not containing Cu.

[0010] In the present application, atomic percentage refers to the percentage of the number of atoms of a certain element in the amorphous alloy, and the unit is at.%, that is, the number of atoms of a certain element is divided by the sum of the number of atoms of all elements to obtain the atomic percentage of the element.

[0011] Preferably, the numerical range of x+y is 80≤x+y≤85, indicating that the added ferromagnetic element atoms account for 80at.% to 85at.%, and not less than 80at.% to maintain a higher saturation magnetic induction intensity of the system; and not more than 85at.%, because when it exceeds, the soft magnetic properties of the entire system will deteriorate, not only its saturation magnetic induction intensity will decrease, but also the amorphous forming ability will weaken, at this time, the α-FeCo phase and the amorphous matrix will coexist, and the coercive force will increase sharply, because the reduction in amorphous forming ability leads to an increase in structural order, increasing the density of quasi-dislocation dipole stress sources or the pinning ability generated by elastic stress, thereby increasing the coercive force.

[0012] Among them, Si, B, P and C are selected as amorphous forming elements. Among them, Si, B, P elements have a large negative mixing enthalpy with Fe elements and are important amorphous forming elements; the mixing enthalpy between C elements and Fe elements is positive, but its atomic radius is small, and it tends to form complex compounds with Fe, B, P during the crystallization process, such as Fe 23 (B, C, P)6, etc., are conducive to obtaining high amorphous forming ability.

[0013] In the iron-cobalt-based amorphous nanocrystalline soft magnetic alloy of the present invention, the atomic percentage of the P element must satisfy: 6≤c≤10. The P element is a common element constituting an amorphous alloy. The P element and other elements in the system have a large negative mixing enthalpy. The addition of the P element is conducive to improving the stability of the supercooled liquid phase, which can not only improve the amorphous forming ability of the alloy, but also improve the thermal stability of the alloy and expand the heat treatment temperature range of the amorphous alloy. The inventors found that when the P element content is less than or equal to 6at.%, the alloy is not completely amorphous. At the same time, when the P element content is greater than or equal to 10at.%, the first crystallization temperature (T x1 ) and the second crystallization temperature (T x2 ), which means that the interval temperature between the ferromagnetic term and the non-ferromagnetic term during annealing is difficult to distinguish, resulting in difficulty in performing the annealing process. Therefore, the present invention limits the value of the atomic percentage c of the P element to: 6≤c≤10.

[0014] The heat treatment temperature of the iron-cobalt-based amorphous nanocrystalline soft magnetic alloy to obtain the best soft magnetic properties is relatively low, lower than T x1 .

[0015] Preferably, the iron-cobalt based amorphous nanocrystalline soft magnetic alloy is a continuous film-like strip.

[0016] Preferably, the thickness of the continuous film-like strip is 17-30 μm.

[0017] Preferably, the continuous film-like strip is an amorphous strip.

[0018] Preferably, the saturation magnetic induction intensity of the iron-cobalt based amorphous nanocrystalline soft magnetic alloy is 1.53T.

[0019] Preferably, the heat-treated iron-cobalt-based amorphous nanocrystalline soft magnetic alloy has nanocrystals, which are uniformly distributed in the microstructure of the soft magnetic alloy and have higher saturation magnetic induction intensity and lower coercive force.

[0020] Preferably, the grain size of the nanocrystals is ≤26 nm.

[0021] Another object of the present invention is to provide a method for preparing the above-mentioned iron-cobalt-based amorphous nanocrystalline soft magnetic alloy, comprising the following steps: S1: According to atomic percentage, 99.99 wt.% high-purity iron, 99.99 wt.% pure silicon, 99.99 wt.% boron, 99.99 wt.% cobalt, 96 wt.% Fe and 4 wt.% C iron-carbon alloy, and 75 wt.% Fe and 25 wt.% P iron-phosphorus alloy are respectively added into a melting furnace, and a master alloy ingot is prepared through a smelting process. The master alloy ingot is melted and condensed for multiple times, and the metal ingot is turned over after each condensation to make the composition of the master alloy ingot uniform; S2: Use steel pliers to break the master alloy ingot or use a wire cutting instrument to cut the master alloy ingot into two; S3: using a single-roller rapid cooling method to prepare the melted mother alloy ingot into a strip-shaped amorphous alloy strip with a width of less than 2 mm and a thickness of less than 30 μm; S4: Cut the amorphous alloy strip into sections with a length of 50 mm each, wrap them with tin foil, fix them with a quartz clamp, and place them in an annealing furnace for annealing heat treatment to obtain a strip-shaped Fe-Co-based amorphous nanocrystalline soft magnetic alloy.

[0022] Furthermore, in the step S1, the furnace used is a non-consumable vacuum arc furnace, the smelting process is carried out under argon protection, and the parent alloy ingot is melted in a furnace equipped with an inverter DC manual arc welding machine using a manual arc welding gun after arcing. The smelting temperature is controlled at 2000-2200°C, the insulation time for a single smelting is 5-20 minutes, and the number of smeltings is ≥3 times; after the smelting is completed, the sample can be taken out after the alloy ingot is fully cooled.

[0023] The master alloy ingot of the present invention has a melting point of 1800-1900°C, and the smelting temperature is controlled to be 200-300°C above the melting point of the master alloy ingot, so the smelting temperature ranges from 2000-2200°C, which can ensure that the alloy material can be fully fused.

[0024] Furthermore, in step S2, the oxide scale on the surface of the master alloy ingot needs to be polished and removed and ultrasonicated before the alloy ingot is crushed. After crushing or wire cutting, ultrasonication is performed again to separate fine impurities generated by crushing from the metal surface.

[0025] Furthermore, the specific process of step S3 is as follows: the crushed master alloy ingot is placed in a quartz tube with a small hole at the lower end, and the vacuum is evacuated to 3×10 -3 Pa, after cleaning the furnace with high-purity argon, fill it with high-purity argon with a pressure difference of 0.08±0.01Mpa, and under its protection, use a high-frequency induction heating coil to heat the metal in the quartz tube to melt it and keep it warm for 5 to 10 seconds to ensure uniform melting, and then perform single-roll melt rapid quenching. When throwing the strip, the linear speed of the copper roller is 34m / s to obtain an amorphous alloy strip.

[0026] Furthermore, in the step S4, the annealing furnace used is an OTF-1200X tubular annealing furnace. The annealing heat treatment temperature used in the present invention is between 340 and 440°C, the heating rate of the heat treatment is 10 to 20°C / min, the annealing time (i.e., the holding time) is 10 minutes, and the annealing atmosphere used is high-purity argon gas, which can be slowly circulated after the tube is filled; before the formal annealing, the amorphous strip obtained in step S3 needs to be wiped to ensure the metallic luster of the strip surface before and after annealing.

[0027] In the present invention application, the soft magnetic alloy can maintain stable soft magnetic properties in a relatively wide heat treatment temperature range, heat treatment heating rate and heat treatment holding time, and has a wide heat treatment process window.

[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) After heat treatment, the soft magnetic alloy component of the present invention has uniform nano-grain distribution, and the soft magnetic properties of the component remain stable under a wide range of heat treatment process conditions, with a saturation magnetic induction intensity greater than 1.43T and a coercive force value less than 15A / m.

[0029] (2) The iron-cobalt-based amorphous nanocrystalline soft magnetic alloy of the present invention has good magnetic properties and excellent thermal stability, and has a wide heat treatment process range, such as a wide heat treatment range and a slow heating rate. It has low requirements for subsequent heat treatment process equipment and is suitable for industrial production.

[0030] (3) The iron-cobalt-based amorphous nanocrystalline soft magnetic alloy of the present invention does not contain metal elements with relatively high costs, such as precious metals, such as Nb, Mo, Zr or rare earth metal elements Y, which can further reduce the cost of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 1 to 6. The XRD patterns of the amorphous alloy strips of Examples 1 to 6.

[0032] Figure 2 The DSC spectra of the amorphous alloy strips of Examples 1 to 6 and Comparative Example 1 are shown.

[0033] Figure 3 The XRD patterns of the amorphous alloy strips heat treated at different temperatures in Example 6.

[0034] Figure 4 Magnetic hysteresis loops of the nanocrystalline ribbon measured in Example 6 after annealing at different temperatures.

[0035] Figure 5 for Figure 4 A localized magnified view of the first quadrant.

[0036] Figure 6 This is the TEM image of Example 6 after annealing at 380°C for 10 min. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0038] The iron-cobalt-based amorphous nanocrystalline soft magnetic alloy provided by the present invention has the following atomic percentage expression: Fe x Co y Si a B b P c C d Cu e ; wherein x, y, a, b, c, d and e represent the atomic percentage of the corresponding element respectively, 60≤x≤70, 15≤y≤25, 3<a≤6, 4<b≤7, 6≤c≤10, 0<d≤1.5, 0≤e≤1, x:y=(3~5):1, and x+y+a+b+c+d+e=100, and the numerical range of x+y is 80~85.

[0039] The following is an example of the present invention using Examples 1 to 6 and Comparative Example 1 to illustrate the properties and protection scope of the soft magnetic alloy of the present invention.

[0040] The components of Examples 1 to 6 and Comparative Example 1 are shown in Table 1, wherein the strip preparation process of each component is carried out according to the preparation method of the present invention, and the heat treatment process parameters adopted are: the heating rate is set to 10°C / min, and the holding time is set to 10min.

[0041] Table 1 Soft magnetic alloy compositions of Examples 1 to 6 and Comparative Examples 1 to 6

[0042] Taking Examples 1 to 6 and Comparative Examples 1 to 6 as examples, the amorphous alloy strip in the present invention is analyzed in detail.

[0043] In the present invention, an X-ray diffractometer (XRD) is used to analyze and verify whether the prepared amorphous alloy strip is a completely amorphous structure. The XRD patterns of Examples 1 to 6 are shown in FIG. Figure 1 As shown in the figure, it can be seen that there is only a broad diffuse scattering peak at a diffraction angle of about 2θ=45°, indicating that the sample has a completely amorphous structure.

[0044] In the present invention, a synchronous thermal analyzer is used to analyze and verify the crystallization temperature of the prepared amorphous alloy strip. The DSC analysis results of Examples 1 to 6 and Comparative Example 1 are shown in Table 2. The analysis spectra are shown in Table 2. Figure 2 As shown in the figure, it can be seen that the DSC curves of the samples have two obvious crystallization peaks. The first crystallization start temperature and the second crystallization start temperature are T x1 and T x2 , and then get ΔT x (Define ΔT x =T x2 -T x1 ). In comparative example 1, the interval between the two crystallization peaks is smaller, which is defined as ΔT x It is basically close to 0. Through the analysis of experimental results, it is found that when the content of metal-like P is high (≥10at.%), the crystallization window (ΔT x ); When Cu element is introduced, the initial crystallization temperature (T x1 ), thereby achieving a wider heat treatment process window in the present invention, which is also consistent with the research results of Tianhaojiang et al. described in the background technology of the present invention.

[0045] Table 2 Crystallization temperature of amorphous alloy strips of Examples 1 to 6 and Comparative Example 1

[0046] From Table 2 and the above results, it can be seen that the amorphous alloy strip of Example 6 has a higher ΔT x As the P content decreases, the first crystallization start temperature gradually decreases, the second crystallization start temperature gradually increases, and the difference between the two crystallization temperatures ΔT x It is constantly increasing; when the alloy does not contain Cu, the amorphous alloy strip basically does not have the first crystallization temperature; this indicates that the heat treatment process window of the amorphous alloy strip of Example 6 is the largest.

[0047] Comprehensive soft magnetic properties test, Table 3 is a comprehensive soft magnetic properties table of amorphous alloy samples of Examples 1 to 6, where B s The saturation magnetic induction intensity is measured by VSM (vibrating sample magnetometer) under an external magnetic field of 16000 Oe (about 1285 kA / m). M s At the same time, the density is calculated using a densitometer. The density measurement results of this type of alloy system are between 7.35 and 7.65, from which the saturation magnetization value of the alloy can be calculated. B s ; and coercivity H c It is measured by using a BH loop instrument; magnetic permeability ( μ e) is obtained by measuring the inductance value at 1kHz using an impedance analyzer and then converting it.

[0048] Table 3 Comprehensive soft magnetic properties of amorphous alloy samples of Examples 1 to 6 and Comparative Examples 1 to 6

[0049] It can be seen from Table 3 that the comprehensive soft magnetic properties of Example 5 and Example 6 are better. If the two are compared, it can be found that Example 5 has higher saturation magnetic induction intensity and relative magnetic permeability (at 1 kHz), while Example 6 has smaller coercive force. This result is essentially due to the fact that limited copper content and appropriate metalloid element content play a vital role in enhancing the stability of the nuclear barrier and the amorphous matrix. This is because insoluble Cu-P clusters are formed in the process of preparing the strip, so that P is enriched between the α-FeCo phase and the matrix, thereby stabilizing the growth of the amorphous matrix and inhibiting the growth and excessive growth of the α-FeCo phase, so that the coercive force can be reduced while ensuring the saturation magnetic induction intensity and relative magnetic permeability (at 1 kHz). At the same time, by observing the comparative examples, it can be found that when the proportion of B element is too high, the magnetic properties of the system deteriorate. This is mainly due to the lack of Cu-P clusters and the immiscible C atoms in the system, which easily occupy the nucleation sites, thereby easily forming Fe-B compounds and deteriorating the magnetic properties. This can be seen from comparative examples 3, 4, and 6. It can be seen that the present invention has an inseparable synergistic effect between the Cu, P, B, and C elements.

[0050] In the present application, the amorphous alloy strip in Example 6 is treated at different heat treatment temperatures, with a fixed heating rate of 10°C / min and a holding time of 10 min. The soft magnetic properties at different heat treatment temperatures are observed, and the results are shown in Table 4.

[0051] Table 4 Effect of different heat treatment temperatures on the soft magnetic properties of amorphous alloy strip of Example 6

[0052] Figure 3 The XRD spectra of the amorphous alloy strip under different heat treatment temperature conditions in Example 6 are shown in Table 4 and Figure 3It can be seen that the grain size remains basically unchanged between 340 and 440°C, and the corresponding coercive force also remains basically unchanged. The saturation magnetic induction intensity increases from 1.43T in the initial quenching state to 1.53T. In the heat treatment temperature range of 340 to 440°C, the saturation magnetic induction intensity, coercive force and magnetic permeability are all in a relatively stable range. When the heat treatment temperature is 420°C, the coercive force reaches a minimum of 7.33A / m; when heat treated at 380°C, the effective magnetic permeability at 1kHz is 2500. This shows that the amorphous alloy strip in Example 6 can achieve better soft magnetic properties at a wider heat treatment temperature of 340 to 440°C. If the heat treatment temperature is lower or higher than this range, the grain size of the amorphous alloy strip will increase significantly, and its corresponding coercive force will also increase significantly, and its soft magnetic properties will decrease significantly.

[0053] Figure 4 and Figure 5 The hysteresis loop spectrum of the nanocrystalline strip measured in Example 6 after annealing heat treatment at 340-440°C shows that the saturation magnetic induction intensity of this type of alloy can be increased with the change of annealing temperature and the hysteresis loop is stable. This also shows that the amorphous alloy strip of Example 6 can maintain a better saturation magnetic induction intensity under a wider heat treatment temperature.

[0054] Figure 6 This is the TEM image of Example 6 after annealing at 380°C for 10 min. The average grain size calculated by the TEM spectrum is about 21 nm, which is consistent with the average grain size calculated by the Scherrer formula, where the peak of α-FeCo in the (110) diffraction plane in XRD is used as the basis for calculation.

Claims

1. An iron-cobalt based amorphous nanocrystalline soft magnetic alloy, characterized in that: The chemical formula of the iron-cobalt based amorphous nanocrystalline soft magnetic alloy is: Fe x Co y Si a B b P c C d Cu e ; Wherein, x, y, a, b, c, d and e represent the atomic percentage of the corresponding element respectively, 60≤x≤70, 15≤y≤25, 3<a≤6, 4<b≤7, 6≤c≤10, 0<d≤1.5, 0≤e≤1, x:y=(3~5):1, and x+y+a+b+c+d+e=100.

2. The iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The numerical range of x+y is 80≤x+y≤85.

3. The iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The soft magnetic alloy is a continuous film-like strip material, the thickness of the continuous film-like strip material is 17-30 μm, and the film-like strip material is an amorphous strip material.

4. The iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The saturation magnetization intensity of the Fe-Co-based amorphous nanocrystalline soft magnetic alloy is B s ≥1.43T, coercivity H c ≤15A / m.

5. The iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The grain size of the nanocrystals of the iron-cobalt-based amorphous nanocrystalline soft magnetic alloy is less than or equal to 26 nm.

6. The method for preparing the iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: S1: According to atomic percentage, 99.99 wt.% high-purity iron, 99.99 wt.% pure silicon, 99.99 wt.% boron, 99.99 wt.% cobalt, 96 wt.% Fe and 4 wt.% C iron-carbon alloy, 75 wt.% Fe and 25 wt.% P iron-phosphorus alloy are respectively added into a melting furnace, and a master alloy ingot is prepared through a smelting process. The master alloy ingot is melted and condensed for multiple times, wherein the metal ingot is turned over after each condensation to make the composition of the master alloy ingot uniform; S2: Use steel pliers to break the master alloy ingot or use a wire cutting instrument to cut the master alloy ingot into two; S3: using a single-roller rapid cooling method, the melted mother alloy ingot is prepared into an amorphous alloy strip with a width of less than 2 mm and a thickness of less than 30 μm; S4: Cut the amorphous alloy strip into sections with a length of 50 mm each, wrap them with tin foil, fix them with a quartz clamp, and place them in an annealing furnace for annealing heat treatment to obtain a strip-shaped iron-cobalt-based amorphous nanocrystalline soft magnetic alloy.

7. The method for preparing the iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: In the step S1, the furnace used is a non-consumable vacuum arc furnace, and the smelting process is carried out under argon protection. The master alloy ingot is melted in a furnace equipped with an inverter DC manual arc welding machine using a manual arc welding gun after arcing. The smelting temperature is controlled at 2000-2200°C, the insulation time for a single smelting is 5-20 minutes, and the number of smeltings is ≥3 times.

8. The method for preparing the iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: In the step S2, the oxide scale on the surface of the master alloy ingot needs to be polished and removed and ultrasonicated before the alloy ingot is crushed. After crushing or wire cutting, ultrasonication is performed again to remove fine impurities caused by crushing from the metal surface.

9. The method for preparing the iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: The specific process of step S3 is: put the crushed master alloy ingot into a quartz tube with a small hole at the bottom, and evacuate to 3×10 - 3 Pa, after cleaning the furnace with high-purity argon, fill it with high-purity argon with a pressure difference of 0.08±0.01Mpa, and under its protection, use a high-frequency induction heating coil to heat the metal in the quartz tube to melt it and keep it warm for 5 to 10 seconds, and then perform single-roll melt rapid quenching. When throwing the strip, the linear speed of the copper roller is 34m / s to obtain an amorphous alloy strip.

10. The method for preparing the iron-cobalt based amorphous nanocrystalline soft magnetic alloy according to claim 6, characterized in that: In step S4, the annealing furnace used is a tubular annealing furnace, the annealing heat treatment temperature is 340-440°C, the heating rate of the heat treatment is 10-20°C / min, the annealing time is 10min, and the annealing atmosphere is high-purity argon.

Citation Information

Patent Citations

  • Iron cobalt-based magnetically soft alloy with high saturation magnetic flux density and preparation method of iron cobalt-based magnetically soft alloy

    CN102925823A

  • Iron-cobalt-based nanocrystalline soft magnetic alloy with excellent comprehensive soft magnetic performance and preparation method of iron-cobalt-based nanocrystalline soft magnetic alloy

    CN116313354A

  • Soft magnetic alloy material, preparation method thereof and inductor using soft magnetic alloy material

    CN118824669A

  • Amorphous soft magnetic alloy

    JP2001316782A

  • Soft magnetic alloy and uses thereof

    WO2008051623A2

Cited By

  • Iron-based amorphous nanocrystalline soft magnetic alloy material as well as preparation method and application thereof

    CN120048609A

  • Method for preparing excellent soft magnetic amorphous nanocrystalline alloy based on lunar soil crystallization phenomenon and soft magnetic amorphous nanocrystalline alloy

    CN120261100A

  • Soft magnetic amorphous alloy capable of reducing high-frequency loss and preparation method

    CN120824092A

  • Amorphous nanocrystalline strip and preparation method thereof

    CN121737600A